The Research Progress in Physiological and Pathological Functions of TRAF4 - Ruan, Xueqin; Zhang, Rong; Li, Ruijuan; Zhu, Hongkai; Wang, Zhihua; Wang, Canfei; Cheng, Zhao; Peng, Hongling (Frontiers in Oncology, 2022)
Tumour necrosis factor receptor-associated factor 4 (TRAF4) is a member of the TRAF protein family, a cytoplasmic bridging molecule closely associated with various immune functions. The physiological processes of TRAF4 are mainly involved in embryonic development, cell polarity, cell proliferation, apoptosis, regulation of reactive oxygen species production. TRAF4 is overexpressed in a variety of tumors and regulates the formation and development of a variety of tumors. In this review, we summarize the physiological and pathological regulatory functions of TRAF4 and focus on understanding the biological processes involved in this gene, to provide a reference for further studies on the role of this gene in tumorigenesis and development.